Pendugaan Komponen Ragam, Heritabilitas dan Korelasi untuk Menentukan Kriteria Seleksi Cabai (Capsicum annuum L.) Populasi F5 - Muhamad Syukur; Sriani Sujiprihati; Rahmi Yunianti; Khaerin Nida (Jurnal Hortikultura Indonesia, 2010)
ABSTRACTInformation on genetic variability and correlation between quantitative characters with yield are important for support the selection program. The objective of the research was to estimate the genetic variability, heritability, and path analysis on agronomic characters to determine the selection criteria in the chili. This research was conducted at Research Station of Leuwikopo, Darmaga, Bogor from November 2009 until May 2010. This research observed all populations i.e. F5 population: 320 plants, IPB C2 population: 20 plants, and IPB C5 population: 20 plants. The results showed that total fruit weight, thick and fruit diameter, middle fruit diameter, blossom end fruit diameter, fruit weight, and days to flowering have a high broad sense heritability . High coefficient of genetic variability values were obtained ini number of fruits per plant, fruit wei ght, stem diameter, fruit diameter, and fruit weight. Based on the heritability, genetic variability, correlations analysis and path analysis, characters that can be used as selection criteria in this study is the number of fruit per plant, fruit weight, and fruit diameter.Key words: genetic variability, heritability, path analysis, selection